Sistem Informasi Pengendalian Informasi Masuk Dan Keluar Pada PUSKESMAS Seberang Padang - Lubis, Muhammad Amrin (STKIP PGRI Sumatera Barat, 2016)
Control information on Community Health Centre Seberang Padang currently has problems in controlling the information that is used today. Those problems include the management for information to someone, not the existence of an information system to process and store data into a database, and the archived information is only information in the form of a letter. For that built an information system to solve the problems on the control of information in and out information on Community Health Centre Seberang Padang, that information needs can be met and served quickly and precisely. The advantages of the proposed system can facilitate the management of information in and out information, the information can be accessed by officers who have id and password so do not depend on one officer. Another convenience is that these applications can store information in digital form such as image, PDF, audio and video